Electrophysiological correlates of integrating choice and response time during sequential decision making. (24th August 2018) - Niu, Xiaofei; Li, Jianbiao; Cao, Qian
Highlights: We explore the neural correlates of integrating choice and response times (RTs) during sequential decision making. P200 and N200 differentiated the Long-RTs from Short-RTs condition. P200 may represent early stage valuations of task-relevant perceptual information. N200 may reflect conflict between participants' prior knowledge and the third person's long RTs. Abstract: Response times (RTs) can provide valuable information about a person's underlying decision processes. To investigate electrophysiological correlates of integrating choice and RTs, ERPs elicited by belief updating in long response times condition (Long-RTs) were compared with those in short response times condition (Short-RTs). In both kinds of conditions, three fictitious persons were arranged in random order ( P1, P2, P3 ) and predicted uncertain state of world. P3 took a long time in Long-RTs condition. In Short-RTs condition P3 rapidly made decisions. Participants' task was to infer P3 's private signal after observing three fictitious persons' same choice and P3 's RTs. ERP results revealed that frontal P200 and N200 distinguished between the two conditions. P200 showed a higher amplitude in Short-RTs condition and might represent early stage valuations of task-relevant perceptual information. N200 showed a more negative amplitude in Long-RTs condition and might reflect conflict between participants' prior knowledge about P3 's private signal and P3 's long RTs. Our study demonstrates that RTs is an indicator of choice and identifies the temporal process of integrating choice and response time during sequential decision making.